COMMUNITY‐BASED WASTE MANAGEMENT - Kusumadinata, Ali Alamsyah (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Waste management is an absolute must do in micro aspects such as village, Neighbor Association, Citizens Association, and the domestic sphere. This management should be managed based on collaboration between the government, public/corporate and private. Waste provide their own assessment among people hence the need for waste management model that is based on existing communities in the village to the central location. This paper is a reflection of the waste collection movement activities conducted in February to April 2015 in the village of Babakan. The findings of this paper is waste is something of value that can be converted into income communities if managed properly. Regulation in the waste needs to be a legal basses in building mutual awareness. Community participation is absolutely the subject of the development of waste so that the model CBSWM (Community Based Solid Waste Management) could be run well.